Limitations of Sulforhodamine 101 for Brain Imaging - Hülsmann, Swen; Hagos, Liya; Heuer, Heike; Schnell, Christian (Frontiers in Cellular Neuroscience, 2017)
Since 2004 the red fluorescent dye Sulforhodamine 101 (SR101) has been boosting the functional analysis of astrocytes in a functional environment in an unprecedented way. However, two major calamities have been challenging the usefulness of this tool for cellular imaging: (i) SR101 is not as specific for astrocytes as previously reported and (ii) discoveries of severe excitatory side effects of SR101 bear the risk of unwanted alteration of the system of interest. In this article, we summarize the current knowledge about this dye and try to shine light on the physiological and pathological implications that arise from the analyses of SR101 stained brain slices.